2019
DOI: 10.1073/pnas.1901893116
|View full text |Cite
|
Sign up to set email alerts
|

A CTG repeat-selective chemical screen identifies microtubule inhibitors as selective modulators of toxic CUG RNA levels

Abstract: A CTG repeat expansion in the DMPK gene is the causative mutation of myotonic dystrophy type 1 (DM1). Transcription of the expanded CTG repeat produces toxic gain-of-function CUG RNA, leading to disease symptoms. A screening platform that targets production or stability of the toxic CUG RNA in a selective manner has the potential to provide new biological and therapeutic insights. A DM1 HeLa cell model was generated that stably expresses a toxic r(CUG)480 and an analogous r(CUG)0 control from DMPK and was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 70 publications
1
39
0
Order By: Relevance
“…Many methods for screening potential medicaments have been studied on DNA, RNA, and protein levels [ 304 , 305 ]. The most numerous and promising group of potential therapeutics is composed of small compounds and antisense oligonucleotides which release sequestered proteins from RNP inclusions due to their high affinity or complementarity to toxic repeats and sometimes induction of degradation of toxic RNA [ 305 , 306 , 307 , 308 , 309 ]. An antisense oligonucleotide-based reagent, ISIS-DMPK-2.5 RX , was the first potential DM1-specific drug which underwent clinical research [ 304 , 310 ].…”
Section: Splicing-related Diseases Mediated By Rna Structural Arramentioning
confidence: 99%
See 1 more Smart Citation
“…Many methods for screening potential medicaments have been studied on DNA, RNA, and protein levels [ 304 , 305 ]. The most numerous and promising group of potential therapeutics is composed of small compounds and antisense oligonucleotides which release sequestered proteins from RNP inclusions due to their high affinity or complementarity to toxic repeats and sometimes induction of degradation of toxic RNA [ 305 , 306 , 307 , 308 , 309 ]. An antisense oligonucleotide-based reagent, ISIS-DMPK-2.5 RX , was the first potential DM1-specific drug which underwent clinical research [ 304 , 310 ].…”
Section: Splicing-related Diseases Mediated By Rna Structural Arramentioning
confidence: 99%
“…An antisense oligonucleotide-based reagent, ISIS-DMPK-2.5 RX , was the first potential DM1-specific drug which underwent clinical research [ 304 , 310 ]. However, due to low therapeutic effect in DM1 patients’ tissues the trial was halted whereas new potential reagents are being intensively screened [ 309 , 311 , 312 , 313 ].…”
Section: Splicing-related Diseases Mediated By Rna Structural Arramentioning
confidence: 99%
“…Given the widespread changes in alternative splicing in mbnl mutant zebrafish, we asked whether these changes were conserved with those identified in human DM patients. Using publicly available datasets, we identified cassette exons for which inclusion was significantly misregulated in DM1 tibialis anterior muscle biopsy tissues ( Wang et al, 2019 ) or in DM1 patient-derived post-mitotic myotubes ( Reddy et al, 2019 ) compared to healthy control tissues, and compared them with the zebrafish RNA-Seq data. We identified 25 orthologous cassette exons that were misregulated in both 1 B/B ;2 A/A ;3 C/C mutant fish and in DM1 tibialis muscle, and 40 that were misregulated in both 1 B/B ;2 A/A ;3 C/C mutant fish and in the DM1 myotubes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The data for human DM1 tibialis anterior comparisons were downloaded from NCBI Gene Expression Omnibus (GEO), accession number GSE86356 (Wang et al, 2019). Data for the DM1-derived postmitotic myotubes were downloaded from NCBI Sequence Read Archive (SRA), study SRP158284 (Reddy et al, 2019). The data were processed as described above and then compared to the zebrafish data for orthologous mis-splicing events.…”
Section: Measurement Of Zebrafish Sizementioning
confidence: 99%
“…In addition to drugs designed to directly target RNA, chemical screens have identified potent modulators of repeat RNA toxicity. Unexpectedly, for example, such tests revealed that multiple inhibitors of microtubule function selectively reduce toxic CUG repeat RNA levels and partially rescue splicing profiles in a DM1 HeLa model ( Reddy et al 2019 ). Subsequent tests of the FDA-approved microtubule inhibitor colchicine in DM1 mice and patient cells revealed a selective modulation of CUG repeat RNA levels, likely a result of impaired cytoskeletal and nucleoskeletal complexes, raising the possibility that colchicine may be useful in treatment of other repeat expansion disorders ( Reddy et al 2019 ).…”
Section: Reductions Of Toxic Rna Levelsmentioning
confidence: 99%